Exploring Interculturality in Algerian Middle School EFL Textbooks - Hairech, Faiza; Belkhir, Yasmina Sakina (Technium Social Sciences Journal, 2022)
Textbooks are indispensable tools for any learning. Teaching and learning a language cannot be dissociated from its culture. Nowadays, proficiency in a language is no more related to grammar mastery, vocabulary, or fluency. Accordingly, language users are presumed to communicate in real-life contexts. Kramsch (1993) stresses the role of both language and culture as components of the latter as considerable in determining and shaping language use and usage. Therefore, it is noticeable that attention is considerably paid to the cultural elements in textbooks’ contents to assure adequate cultural understanding. Course books are also media for socializations as they vehicle the socio-cultural norms of the foreign language to be taught. Intercultural competency may be acquired from the content through different aspects (linguistic, visual). EFL textbooks content is not exclusively restricted to linguistic knowledge, but also has the objective of developing an intercultural competence of the target language among their learners. The pupils are in exposure to the target culture, yet their age (11-14) is critical as they might not be able to evaluate some cultural aspects that may collide with the home culture. In this prospect, we investigate how intercultural competence is articulated and presented in the four middle school textbooks of English (My book of English: First, second, third, and fourth levels). Our aim is to verify whether textbooks used for teaching English as a foreign language in Algerian public schools employ an intercultural approach, by examining how both the target and source cultures are depicted. The research tools that we used are checklists. Checklists were used in texts analyses to elicit the cultural aspects presented in the content.